2010
DOI: 10.1111/j.1574-695x.2010.00705.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitroeffect of branch extracts ofJuniperusspecies from Turkey onStaphylococcus aureusbiofilm

Abstract: Methanol and aqueous branch extracts of five Juniperus species were examined for their effects on Staphylococcus aureus ATCC 6538P and S. aureus 810 biofilm. The Turkish plant material was Juniperus communis L. var. communis, J. communis L. var. saxatilis Pall., Juniperus drupacea Labill., Juniperus oxycedrus L. ssp. oxycedrus, J. oxycedrus L. ssp. macrocarpa (Sibth. & Sm.) Ball. The Juniperus extracts were subjected to preliminary phytochemical analysis by thin-layer chromatography. The antimicrobial activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…For example, Marino et al evaluated in vitro effect of branch methanol and aqueous extracts of five juniperus species on the growth, adherence, and biofilm formation of S. aureus. All the extracts affected the biofilm development depending on the biofilm-forming strain capacity and, in our study, inhibited bacterial growth of all assayed strains [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Marino et al evaluated in vitro effect of branch methanol and aqueous extracts of five juniperus species on the growth, adherence, and biofilm formation of S. aureus. All the extracts affected the biofilm development depending on the biofilm-forming strain capacity and, in our study, inhibited bacterial growth of all assayed strains [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Terpenoids, glycosteroids, flavonoids, and polyphenols are small molecules naturally produced by plants that can inhibit many bacterial species, particularly gram-positive organisms. These compounds are receiving sustained attention regarding their potential use since there has been strong evidence that they possess, in addition to antimicrobial activity, anti-inflammatory and antitumour properties [ 22 , 28 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…The optical density of well contents was determined using a Multiskan Go UV Spectrophotometer set at 570 nm. Biofilm inhibition was calculated using a formula (Equation 1) suggested by Marino et al (2010):…”
Section: Inhibition Of Xoo Biofilm Formation By Ammh Leaf Extractmentioning
confidence: 99%
“…The antibacterial properties of plant-derived compounds have also been attracting attention, mainly in view of the increased antibiotic resistance both in hospitals and in community-acquired infections (Moellering, 2006;Gould, 2008). Several studies reported the antibacterial activity of flavonoid-rich natural products, including propolis (Koru et al, 2007), nuts (Mandalari et al, 2010a,b), Juniperus extracts (Marino et al, 2010;Miceli et al, 2011), grape seeds (Adamez et al, 2012) and Citrus plants (Mandalari et al, 2007). The identification of new compounds with bactericidal rather than bacteriostatic effect has gained understandable interest, together with the several recent reports of flavonoids increasing the activity of antibiotics through synergistic interactions (Bernal et al, 2009;D'Arrigo et al, 2010;Eumkeb et al, 2010).…”
Section: Introductionmentioning
confidence: 99%